Efficient photocatalytic oxidative deamination of imine and amine to aldehyde over nitrogen-doped KTi3NbO9 under purple light. Issue 19 (25th August 2020) - Yu, Zhuobin; Gu, Xianmo; Wang, Ruiyi; Wang, Jie; Zhao, Jian; Pei, LinJuan; Zheng, Zhanfeng
Abstract : Nitrogen doped titanoniobate (N-KTi3 NbO9 ) exhibits excellent performance in photocatalytic oxidative deamination of imine and amine to aldehyde. Abstract : KTi3 NbO9 nanoparticles were fabricated via a simple hydrothermal method with a post-calcination treatment. The nitrogen doping (N-KTi3 NbO9 ) leads to a narrow band gap, which in turn facilitates efficiently catalysis of imine deamination under purple light that matches its absorption spectra. Furthermore, N-KTi3 NbO9 exhibits excellent performance in the tandem reaction of photocatalytic imine formation and deamination from various amines. The conversion of benzylamine was up to 100% with >85% benzaldehyde selectivity.